Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

-3 (n - 5) = 3 (1 - 3n)

Sagot :

Answer:

n = -2

Step-by-step explanation:

-3 (n - 5) = 3 (1 - 3n)

Distribute

-3n +15 = 3 - 9n

Add 9n to each side

-3n+15 +9n = 3-9n+9n

6n +15 = 3

Subtract 15 from each side

6n+15-15 =3-15

6n = -12

Divide by 6

6n/6 = -12/6

n = -2

suspho

Answer:

n = -2

Step-by-step explanation:

-3 (n - 5) = 3 (1 - 3n)

-3n + 15 = 3 - 9n

-3n + 9n = 3 - 15

-6n = -12

n = -2

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.